Study of Mental Health Status of the Resident Physicians in China During the COVID-19 Pandemic - Jia, Shuang-Zhen; Zhao, Yu-Zhen; Liu, Jia-Qi; Guo, Xu; Chen, Mo-Xian; Zhou, Shao-Ming; Zhou, Jian-Li (Frontiers in Psychology, 2022)
Objective Investigating the mental health status of Chinese resident physicians during the 2019 new coronavirus outbreak. Methods A cluster sampling method was adopted to collect all China-wide resident physicians during the epidemic period as the research subjects. The Symptom Checklist-90 self-rating scale was used to assess mental health using WeChat electronic questionnaires. Results In total, 511 electronic questionnaires were recovered, all of which were valid. The negative psychological detection rate was 93.9% (480/511). Among the symptoms on the self-rating scale, more than half of the Chinese resident physicians had mild to moderate symptoms of mental unhealthiness, and a few had asymptomatic or severe unhealthy mental states. In particular, the detection rate of abnormality was 88.3% (451/511), obsessive-compulsive symptoms was 90.4% (462/511), the sensitive interpersonal relationship was 90.6% (463/511), depression abnormality was 90.8% (464)/511), anxiety abnormality was 88.3% (451/511), hostility abnormality was 85.3% (436/511), terror abnormality was 84.9% (434/511), paranoia abnormality was 86.9% (444/511), psychotic abnormalities was 89.0% (455/511), and abnormal sleeping and eating status was 90.8% (464/511). The scores of various psychological symptoms of pediatric resident physicians were significantly lower than those of non-pediatrics (p < 0.05). Conclusion The new coronavirus epidemic has a greater impact on the mental health of Chinese resident physicians.